Foreign direct investment and economic growth in South America. Issue 2 (4th March 2019) - Owusu-Nantwi, Victor; Erickson, Christopher
Abstract : Purpose: The purpose of this paper is to investigate the impact of foreign direct investment (FDI) on economic growth in countries in South America. Additionally, the study explores the causal linkage between FDI and growth in the region. Design/methodology/approach: The study employs Pedroni's cointegration test to examine the long-run relationship between FDI and economic growth in South America. Further, the study employs the vector error correction model (VECM) to examine the long-run relationship, and the causal nexus between FDI and economic growth in South America for the period 1980–2015. Findings: The Pedroni cointegration test establishes a long-run relationship between FDI and economic growth in a panel of ten countries in South America. The long-run estimates of the study find a significant positive impact of FDI on economic growth in the region. The VECM results find a short-run bidirectional causality between FDI and economic growth. The error-term is negative and significant. This indicates the presence of long-run equilibrium relationship among the variables. Practical implications: Countries in South America should adopt policies that would substantially enlarge FDI inflows to enhance their growth and development. Originality/value: Numerous studies have examined the impact of FDI on economic growth in the context of Latin America. This study fills a gap in the existing literature by providing an empirical evidence that focuses on South America. This additional perspective could form the basis for the evaluation of the investment policies, and help policymakers to pursue FDI policies that would enhance growth and development in South America.